Determination of biologically active substances in protein-berry concentrates - Grek, Olena; Onopriichuk, Olena; Pshenychna, Tetyana; Tymchuk, Alla (My University, 2018)
Досліджено поліфенольний склад і проаналізовано порівняно з контролем (пастою чорносмородиновою) та визначено ступінь переходу в концентрати білково-ягідні, що складає близько 55,31 % поліфенольних сполук, в тому числі антоціанів. Білки концентратів мають повноцінний амінокислотний склад і містять всі незамінні амінокислоти, вміст яких від загальної суми становить для білково-ягідних та молочно-білкових – 41,97 % та 43,96 % відповідно. В концентратах ідентифіковано 18 вільних та 16 зв’язаних амінокислот, із яких переважають глютамінова кислота, гістидин, метіонін, лейцин та пролін. Визначено замінні амінокислоти, вміст яких від суми загальних амінокислот в КБЯ та КМБ (контроль) становить 58,03 % та 56,04 %. Збільшується вміст НАК в концентратах білково-ягідних на 14,75 % та ЗАК на 24,45 % за наступними амінокислотами: треонін на 0,156 мг%, лізин на 0,21 мг%, триптофан на 0,221 мг%, фенілаланін – 0,525 мг% порівняно з контрольним зразком. The research results of polyphenol composition were analyzed compared with the control (blackcurrant paste) and the degree of their transition to protein-berry concentrates was determined, which is about 55.31 % of polyphenols, including anthocyanins. Proteins in concentrates have a full amino acid composition and contain all essential amino acids, the content of which from amount is 41.97 % and 43.96 %, respectively, for protein-berry and milk-protein. A quantitative content of 18 free amino acids and 16 bound amino acids has determined in protein-berry and milk-protein concentrates, of which glutamic acid, histidine, methionine, leucine and proline are dominated. The nonessential amino acids were determined, the content of which is 58.03 % and 56.04 % from the sum of total amino acids in the PBC and MPC (control). The content of essential amino acids in protein-berry concentrate has increased by 14.75 % and the nonessential amino acids by 24.45 % by the following amino acids: threonine at 0.156 mg%, lysine at 0.21 mg%, tryptophan at 0.221 mg%, phenylalanine at 0.525 mg% compared with the control sample.
Determination of biologically active substances in protein-berry concentrates
Keywords: білки; ягоди; коагуляція; поліфеноли; амінокислоти; protein; berry; coagulation; polyphenols; amino acid; кафедра технології молока і молочних продуктів